An Active/Reactive Power Control Strategy for Renewable Generation Systems - Andrade Aguero, Ivan Eric; Pena, Ruben; Blasco-Gimenez, Ramon; Riedemann, Javier; Jara, Werner; Pesce, Cristian (My University, 2021)
The development of distributed generation, mainly based on renewable energies, requires the design of control strategies to allow the regulation of electrical variables, such as power, voltage (V), and frequency (f), and the coordination of multiple generation units in microgrids or islanded systems. This paper presents a strategy to control the active and reactive power flow in the Point of Common Connection (PCC) of a renewable generation system operating in islanded mode. Voltage Source Converters (VSCs) are connected between individual generation units and the PCC to control the voltage and frequency. The voltage and frequency reference values are obtained from the P-V and Q-f droop characteristics curves, where P and Q are the active and reactive power supplied to the load, respectively. Proportional-Integral (PI) controllers process the voltage and frequency errors and set the reference currents (in the dq frame) to be imposed by each VSC. Simulation results considering high-power solar and wind generation systems are presented to validate the proposed control strategy.
Keywords: power control; power conversion; reactive power control; renewable energy sources